O amor tudo suporta? o papel dos mitos do amor romântico e do sexismo na invisibilidade do abuso psicológico contra a parceira - Silva, Francicléia Lopes (2024)
Psychological abuse differs from other forms of violence because it does not leave visible marks and, for this reason, is sometimes not perceived as violence per se. Thus, this thesis aims to investigate the psychosocial aspects that hinder the perception of psychological abuse as a type of violence. We hypothesize that ambivalent sexism, together with romantic love myths, are beliefs that act to hinder the perception of this type of violence. Additionally, we expect that the relationship between these variables occurs differently in Brazil and Spain. Therefore, this thesis has been organized into three articles. Article 1, composed of two studies, aimed to develop a measure to assess the perception of psychological abuse against partners (EPAPP; total N = 384 participants). The first study confirmed the adequacy of a bifactorial model of the instrument (Emotional Abuse, = 0.91; Control Abuse, = 0.89), which was corroborated in the second study, which also showed convergent validity of the instrument with the ambivalent sexism scale. Article 2 was a quasi-experimental 2x2x2 study, developed with a Brazilian population, and involved the participation of 214 university students. This article aimed to verify if sexism together with romantic love myths explain the perception of psychological abuse. The results illustrated an interaction between the type of abuse and the myths of romanticism, which resulted in a decrease in the perception of emotional abuse against the partner in EPAPP. Additionally, high adherence to sexism moderated the perception of psychological abuse. Article 3 replicated Article 2 in the Spanish context and had a sample of 211 people from the general population. The results reinforced the evidence that psychological abuse is less perceived by people with high adherence to sexism. The results also indicate that sexism has a moderating power in the relationship between experimental manipulations of romantic love myths and the perception of psychological abuse. The differences between the investigated countries focused on the impact of romantic love myths. In Brazil, these myths affected the perception of abuse only when combined with the manipulation of emotional abuse, while in Spain, they affected only when associated with the moderation of sexism. This highlights the need for interventions primarily focused on sexism, which has a direct effect on the perception of abuse.